KELAS KOMUNITAS MENUNJANG TERCIPTANYA KARAKTER KOMUNIKATIF PESERTA DIDIK HOMESCHOOLING PALEMBANG - Fajri Kafarisa, Rosda; Kristiawan, Muhammad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
This paper aimed at investigating the communicative character of learners that could be seen in the pleasure of talking, socializing and cooperating with others in the community class conducted by Homeschooling Primagama Palembang every Saturday morning. This paper was qualitative descriptive. The data were obtained in the form of observation, interview and documentation results compiled from the location of observation. The results showed that the existence of a community class held every once a week, made students of Primagama Homeschooling could work together and mingle neglecting the age and education, and can socialize with the surrounding environment.